2021
DOI: 10.1016/j.asmr.2020.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Novice Surgeon Portal Preference to Visualize the Femoral Anterior Cruciate Ligament Footprint: The Accessory Medial Portal Offers Improved Visualization

Abstract: Purpose To evaluate participant opinions on the appropriateness of different viewing angles by asking 8 questions, using visual content techniques. Methods Survey information from participants was used in this study. We used images of a patient who was operated on for symptomatic knee instability. Participants were asked whether the visual angle could determine the femoral tunnel entry point or evaluate anterior cruciate ligament (ACL) integrity. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Regarding the portal usage to visualize femoral footprint and establish femoral tunnel Our survey has a broad consensus that surgeons prefer the AL portal over AM portal to visualize femoral footprint (Tables 4, 5). Although the AL portal remains a preferred portal to visualize and establish the femoral tunnel, several authors suggest visualization via AM portal as that provides an orthogonal view of the femoral footprint rather than an oblique or tangential view from the AL portal, and that may help in more precise identification of the footprint [20,21]. However, a recently concluded study found no difference between the two techniques [22].…”
Section: B) Intra-operative Trendsmentioning
confidence: 99%
“…Regarding the portal usage to visualize femoral footprint and establish femoral tunnel Our survey has a broad consensus that surgeons prefer the AL portal over AM portal to visualize femoral footprint (Tables 4, 5). Although the AL portal remains a preferred portal to visualize and establish the femoral tunnel, several authors suggest visualization via AM portal as that provides an orthogonal view of the femoral footprint rather than an oblique or tangential view from the AL portal, and that may help in more precise identification of the footprint [20,21]. However, a recently concluded study found no difference between the two techniques [22].…”
Section: B) Intra-operative Trendsmentioning
confidence: 99%